MECHANICAL PARAMETERS CONTROL OF THE NEUTRAL RELAY OF RAIL AUTOMATICS BASED ON WAVELET ANALYSIS - Havryliuk, V. I. (Science and Transport Progress, 2016)
Purpose. The scientific paper focuses on development of a method for mechanical parameters control of the neutral relay of rail automatics by current analyzing in the coil and the relay contacts at switching based on wavelet transform. Methodology. The methodology was based on current analysis of the relay coil and contacts currents under its switching and analysis obtained results by using wavelet transform. Findings. The time dependences of the current in coil and in contacts under switching on and off for the operable relays and relays with certain defects have been measured at different voltages applied to coil (10, 12 и 14 V). When voltage applied to coil was increased the rate of coil current increased, but time constant of the circuit was changed with voltage slightly. The current value maximum at which the relay armature begun to move for the operable relays was depended on applied voltage slightly. For the time interval, at which armature was putted to the relay core fully, time constant of the circuit was changed with voltage slightly also. The maximum current value at which the armature starts to move to the relay serviceable little dependent on the applied voltage. For site based in which the anchor is completely dragged constant current rise time is also a little dependent on the applied voltage. Similar results were obtained for the current reduction time constant with turning off the voltage and current confinement. The current pick-up and the current release of the armature increases for the relay with the load anchor is proportional to the weight of cargo, as well as for the relay contact with the rear, bent down, while the flexural rear contact up these currents have smaller values. Large-scale (low-frequency) coefficients of DWT can be used for a more accurate comparison of the current pick-up, and release time constants of the transient. Small scale coefficients fiberboard (HF) can be used as distinguishing traits defects mobile relay system. Originality. For the first time, on the basis of the research proposed to use detailing coefficients of a discrete wavelet transform as a symptom of mobile relay system. The approximation (smoothing) ratios can be used for a more accurate comparison of the current pick-up, and release time constants of the transient to detect defects of the electromagnetic relay system. Practical value. The studies conducted by the author can be used to develop stand-aided control of a technical condition of the relay neutral railway automation.